Sosialisasi Proses Importasi: Perbaikan Data Inward Manifest Pada Perusahaan XYZ Internasional Kargo - Sujana, Putria Maury; Susanto, Primadi Candra; Sembiring, Honny Fiva Akira; Chaeruddin, Irwan; Fahriza, Basri (Jurnal Abdimas Transportasi & Logistik, 2024)
This community service activity titled “Socialization of the Importation Process: Improvement of Inward Manifest Data at XYZ International Cargo Company” was conducted to address operational inefficiencies and data inaccuracies in the company’s import documentation process. The background of this program stems from the frequent errors found in inward manifest data entry, which often cause shipment delays, additional administrative costs, and decreased service quality. The main objective of the activity was to enhance the participants’ understanding of the importance of accurate data management and the procedures for improving the inward manifest process according to applicable regulations. The activity was carried out through an online workshop involving logistics practitioners, import-export staff, and document administrators. The method used combined interactive presentations, case discussions, and direct practice simulations on the company’s system. The results showed a significant increase in participants’ comprehension and awareness regarding the importance of synchronization between documentation and customs systems. Participants also demonstrated better accuracy in data validation during simulations. In conclusion, this program succeeded in improving both knowledge and practical capabilities of employees, contributing to smoother import operations and supporting the company’s goal of achieving higher service efficiency and compliance with international logistics standards.